Chronic Energy Deficiency Mediates the Effect of Socioeconomic Status on Anemia in Pregnancy: A Case-Control Study in Rural Gorontalo - St. Surya Indah Nurdin; Sitti Mukarramah; Zul Fikar Ahmad; Yuliandary Yunus (Direktorat Politeknik Kesehatan Makassar, 2026)
Anemia during pregnancy remains an important public health problem and is closely associated with socioeconomic inequality and maternal nutritional status. This study aimed to examine the role of chronic energy deficiency (CED) as a potential mediator in the relationship between socioeconomic status and anemia among pregnant women in rural Gorontalo, Indonesia. An observational analytic study with a case–control design was conducted involving 168 pregnant women, consisting of 56 anemia cases and 112 non-anemic controls, selected using consecutive sampling. Cases were defined as pregnant women with hemoglobin levels <11 g/dL, while controls were pregnant women with hemoglobin levels ≥11 g/dL. Data were obtained from primary data collection and maternal health records. Causal mediation analysis guided by a directed acyclic graph (DAG) was performed using logistic regression to estimate the adjusted total effect, natural direct effect, and natural indirect effect. After adjustment for potential confounders, low socioeconomic status was significantly associated with anemia during pregnancy, with a total effect of aOR = 4.05; 95% CI: 1.841–8.896. The natural indirect effect through CED was also statistically significant, with aOR = 1.31; 95% CI: 1.018–1.693, accounting for 23.76% of the total effect. The natural direct effect remained significant, with aOR = 3.08; 95% CI: 1.351–7.030. These findings indicate that CED partially mediates the relationship between socioeconomic status and anemia during pregnancy. Anemia prevention strategies should therefore integrate maternal nutritional interventions with broader socioeconomic and antenatal care approaches, particularly for pregnant women from socioeconomically disadvantaged backgrounds.